An Examination of eHealth Literacy among Adults in an Intergenerational Context (Third Sector Social Economic Review, 2026)
This study aims to examine how eHealth literacy varies across generations and to do so using both parametric analyses and data-driven classification methods. The study used data collected via a survey from 561 participants across the X, Y, and Z generations living in Istanbul. First, an ANOVA was conducted to examine variation in eHealth literacy across generations. Subsequently, K-means cluster analysis was performed to investigate how eHealth literacy clustered within the data. In the final stage, cross-tabulation and chi-square analysis were used to test the significance of the relationship between the resulting clusters and the generations. The ANOVA results showed a significant difference between generations. Generation X had lower eHealth literacy scores than other generations; no significant difference was observed between Generations Y and Z. The cluster analysis identified three clusters of eHealth literacy: low, medium, and high. The chi-square test revealed a significant relationship between generations and clusters. Generation X was mainly represented in the medium-low eHealth literacy cluster, Generation Y was primarily described in the medium eHealth literacy cluster, and Generation Z was mainly represented in the high eHealth literacy cluster. The findings show that eHealth literacy differs significantly across generations. Generation Z stands out as the group with the highest eHealth literacy, while Generation X has relatively lower eHealth literacy. The results indicate that differentiated approaches are necessary in the design of generation-based digital health education and eHealth applications.
Keywords: eHealth; eHealth Literacy; Generation X; Generation Y; Generation Z